Rüzgar Enerjisi Yatırım Projelerinde Finansman Seçeneklerinin Karşılaştırılması - Başar, Güngör (Fen Bilimleri Enstitüsü, 2015)
Günümüzde enerji üretiminde yoğun olarak kullanılan fosil enerji kaynaklarının, öngörülere göre yakın gelecekte tükenecek olması, bu yakıtların kullanımının sera gazı salınımlarını arttırarak küresel ısınma başta olmak üzere, hava ve su kaynaklarının kirlenmesi gibi çevresel etkilerinin olması, ülkeleri yenilenebilir enerji kaynaklarına yöneltmiş ve geçtiğimiz yıllarda özellikle rüzgar enerjisi sektöründe önemli gelişmeler yaşanmıştır. Büyük ve küçük ölçekli rüzgar türbinleriyle uzaktaki yerleşim yerlerine, konutlara ve şebekeye elektrik sağlayan, temiz ve yenilenebilir enerji kaynağı olan rüzgar enerjisi, dünyanın en hızlı büyüyen enerji kaynağı durumuna gelmiştir. Rüzgar enerjisi sektöründeki bu hızlı gelişim ise, devletlerin izlemiş oldukları yenilenebilir enerji sektörünü canlandırmaya yönelik; vergi indirimi, arazi kiralama ve yatırımın ilk yıllarındaki yükümlülükleri hafifletme, yenilenebilir enerji kaynaklarından üretilen elektriğe sabit fiyatla alım garantisi uygulama gibi teşvik senaryolarına ve finans kuruluşlarının farklı finansman modelleri uygulayarak yatırımlara olanak sağlamasından kaynaklanmaktadır. Özellikle proje finansmanı ile, uzun vadeli ve büyük hacimli yatırımların finansman ihtiyacınının karşılanmakta, yeterli sermaye birikimine sahip olmayan yatırımcıların projelerini hayata geçirmeleri sağlanmaktadır. Bu tez kapsamında, bir rüzgar enerjisi projesinin; yenilenebilir enerji yatırımcılarına sağlanan lisans bedeli, arazi kira bedeli indirimi, üretilen elektriğin devlet tarafından sabit fiyatla alımı ve yerli üretim desteği gibi teşvikleri kapsayacak şekilde bir finans modeli oluşturulmuştur. Kredi ve özkaynak kullanımı oranlarının değişimine bağlı olarak, yatırımcının projeye yatırım kararı almadan önce değerlendirdiği karar yöntemlerinden; net bugünkü değer, iç karlılık oranı, geri ödeme süresi ve karlılık endeksinin değişimi araştırılmıştır. Net bugünkü değer yöntemine göre karar alan yatırımcılar için en karlı finans modelinin, projenin tamamıyla özsermaye ile gerçekleştirilmesi olduğu ortaya konurken; kredi kullanmayı düşünen yatırımcılar için, proje maliyetinin yüzde otuza kadarlık kısmının kredi ile karşılanmasının projenin ekonomik olmasını sağlayacağı gösterilmiştir.  Bunun yanında proje gerçekleştirme sürecinde kredi kullanıldığı taktirde, kredi borcunun ödemesinin, yıllar geçtikçe azalan miktarda anapara ödemesi ve değişken kredi taksidiyle gerçekleştirilmesinin, projenin kredi yükünü azaltarak, projeden daha ekonomik sonuçlar alınmasını sağlayacağı gösterilmiştir. Ayrıca projenin karlılığını doğrudan etkileyen faktörlerden santral kapasite faktöründeki artışın, projenin net bugünkü değeri ve iç karlılık oranını pozitif olarak etkilediği ispatlanmıştır.

Depending on the development of modern requirements and technology field, electricity consumption is increasing day by day. In addition, the rapid increase in world population brings up the issue of energy need. According to the projections, fossil energy sources, which are heavily used in power generation at the present time, will be depleted in near future and this is one of the most important factors threatening the security of energy supply.  Moreover, as the use of fossil fuels increases the greenhouse gas emissions and causes particularly global warming, environmental impacts such as pollution in air and water resources; while countries do their energy planning for next years focus on clean and sustainable alternative energy sources which are called also renewable energy sources instead in order to reduce the energy production from fuel based energy sources.  Significant developments have been carried out in renewable energy sector especially in wind energy industry in the past few years and so many wind energy power plants were established in many countries. Wind energy as a renewable energy source, provides electricity to grid, remote settlements and dwellings with large and small-scale wind turbines, has become clean and the world's fastest growing energy source. This study presents the current status and future aspects of wind energy at global and local level, considering various aspects such as resource potential, installed capacity, economics and policies related to primarily to climate change. Rapid growth in wind energy industry is due to incentive policies; tax breaks, discount in land leasing fee and mitigation of some obligations in first years of the project and fixed price to purchase electricity generated from renewable energy sources, has been followed by states and is due to applied different financing models to enable investments by financial institutions. Especially with the project financing, financing need of large volume and long term investments and investors who do not have enough capital to implement the project are met. At that point, investors face with questions such as how the project will be funded, in what proportion the loan should be used and in which way, that makes project worth to invest, this loan should be paid. Project evaluation methods such as net present value, internal rate of return, payback period method are performed during investment decision are made to analyze profitability of the project. Electricity selling prices, the average wind speed of region where the wind park is installed, ground conditions and the proximity to the transmission network and turbine prices need to be taken into account by investor during project analysis process since all those factors affect the result of the analysis and also investment decision of investors. In this thesis, a finance model of the wind project which covers some incentive policies such as reduction of licence fee and land rent, purchasing of the electricity generated from renewable energy sources with  fixed price and local manufacturing was set.  Decision criterias used in investment projects depending on financial structure of the project has been investigated. Variables which may appear in financial structure have been mobilized and the variations in the profitability of the equity capital have been analyzed.  A dynamic finance model which was prepared for example wind project has been assessed accordingly. The change in net present value, internal rate of return, change of payback period and profitability index, which are evaluated by investor during the project analysis, depending on the change of use of loan and equity ratios.  Proved that the most profitable way of realization of the project for investors who make decision according to net present value method is fully financed of the project from investors' equity.  As there is no credit cost occurs in case the project is financed by investors' capital completely, this will prevent reduction in project profit and investors will make more profit from the project.  Investors who have an intention to use loan because of financial structure, investment strategy, lack of capital etc., it is shown in this study that the project which is carried out with the loan as much as thirty percent of project cost makes the project more economical in comparison to higher credit usage ratios. Profitability index which is another economic decision making criteria also have been evaluated and the profitability index of the sample wind energy project has been calculated. According to the financial model, the profitability index of the project is bigger than 1 which means the sample project worths to be invested in. One of the factors which affects the profitability of an investment project is how the used credit should be paid back. In the model formed in this thesis, four different loan repayment methods have been formed and net present value and internal rate of return of the project have been calculated again according to those loan repayment methods.  According to the finance model which was formed in this thesis, if repayments of loan debt is carried out by decreasing the amount of capital payments and variable loan installments in the following years of payment period whether loan is used ın the process of project realization, it allow the project be more feasible as the total interest amount paid will be less than other repayment methods. Importance of the capacity factor for profitability of wind energy project is also one of the topics which had been evaluated in this thesis. For that reason, a capacity factor range (%25 - %47) defined and then net present value, internal rate of return and payback period of the sample wind project has been calculated according to capacity factor values in this range. It was demonstrated that the increase in the capacity factor of the wind park, which influences profitability of the project, affects the net present value and internal rate of return of the project positively. These results prove the importance of accurate project development in terms of selection of wind project location and wind turbine. The financial model which was created in this study basis on benefitting from renewable energy incentives of Turkey by means of selling electricity with fixed price and local manufacturing.  Investors who carry out the wind project with wind turbines whose entire or some components are manufactured locally will benefit from local manufacturing incentive and sell the electricity with higher prices at first five years of the project. This affects the project profitability positively as the income will be higher under those circumcıtances. In future, analysis of the effectiveness of renewable energy incentive policy of Turkey can be investigated and detailed studies can be brought in literature. Investors who have not make decision on choosing local or imported wind turbine can benefit from those studies and incorporate those results to their financial models and see the positive or negative affect of renewable energy incentive. In addition to this, in order to analyze the affects of credit usage on investment decision criterias, comparing different interest rates with different credit repayment methods will make important contribution to the literature. Evaluation of the variation of net present value, internal rate of return, profitability index of the investment project according to the different project finance models such as ECA credits or local credit usage can help investors to form their own project finance model and overcome financing problems.
Comparison Of Financing Options In Wind Energy Investment Projects
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Rüzgar; Yenilenebilir Enerji; Net Bugünkü Değer; Özkaynak Oranı; İç Karlılık Oranı; Geri Ödeme Süresi; Karlılık Endeksi; Kapasite Faktörü; Wınd Energy; Renewable Energy; Net Present Value; Equıty Ratıo; Internal Rate Of Return; Payback Perıod; Profıtabılıty Index; Capacıty Factor